EFEITO SEDATIVOANESTÉSICA DO ÓLEO ESSENCIAL DE Lippia origanoides PARA JUVENIS DE CURIMBA Prochilodus lineatus - CHAVES, Naira luz Souza; SILVA, Maria Eduarda Mendes Vasconcelos; XAVIER, Vitória Maria Gregório; ACUNHA, Rubia Mara Gomes; OLIVEIRA, Fulvia Cristina; CAMPOS, Cristiane Meldau (ANAIS DO ENIC, 2026)
.